Three-dimensional mechanics of the rugby tackle, does the ball carrier alter their movement into contact in response to the tackler`s position - Edwards, S.; Tahu, T.; Buchanan, M.; Tucker, R.; Fuller, G.; Gardner, A. J. (International Journal of Sports Science & Coaching, 2022)
In rugby league and rugby union, the ball carrier is vulnerable to injury during a tackle. The height of the tackle has been associated with injury risk. The extent to which a ball carrier may alter their approach entering a tackle in response the tackler s body height is unknown. This exploratory study aimed to identify if, when and how, the ball carrier modified their motion when being tackled in response to tackling instructions given to the tackler. Three-dimensional analysis was completed on 15 adult male rugby union/league players performing a front-on, one-on-one tackle at differing tackle heights. Repeated measure factorial analyses of variance were used to test for differences (P < 0.05). The ball carrier used two movement strategies: (1) increasing their stability by flexing their trunk, knee, and hips more when entering mid/high torso tackles; (2) offloading the ball or performing an evasive movement strategy by positioning themselves in a more upright body position when being tackled at a lower torso tackle height. This preliminary evidence suggests it may be beneficial for a coach to provide different instructions to the ball carrier to modify their movement strategies when being tackled in response to the height of the tackler to improve their performance and decrease their potential injury risk.